"Epidemic Outbreak of Cutaneous Leishmaniasis due to Leishmania major in Ghanavat Rural District, Qom Province, Central Iran" - AA Akhavan; MR Yaghoobi-Ershadi1; D Mehdipour; H Abdoli; B Farzinnia; M Mohebali; H Hajjaran (Tehran University of Medical Sciences, 2003)
An outbreak of zoonotic cutaneous leishmaniasis caused by Leishmania major was identified in Ghanavat rural district, Qom province, central Iran, during 1999-2001. Among 1069 inhabitants examined in Dec. 1999, 5.14% showed evidence of active lesions and 12.44% had scar indicative of past infection. The most highly infected age group was 5-9 years old for ulcers with a rate of 6.56%. The incidence of the disease was calculated as 2.7% and 1.4% in 2000 and 2001 respectively. Meriones libycus (66.7%), Nesokia indica (27.3%) and Hemechinus aurithis (6%) were present around the district. No leishmanial infection was seen in the slides. Meriones libycus is the probable reservoir host of the disease in the area. Sixteen dogs appeared to be uninfected because examination showed no active lesion or scar. Most probably Phlebotomus papatasi is the vector because 81.53% of indoor sand flies were of this species. The active season of P.papatasi was from late April to early October in indoors. The occurrence of this outbreak of ZCL in the district seems to be the result of construction of buildings near colonies of rodents and also traveling to other infected foci of Iran.